Organic-Inorganic Geochemical Characteristics of the Upper Permian Pusige Formation in a High-Saline Lake Basin, Tarim Basin: Implications for Provenance, Paleoenvironments, and Organic Matter Enrichment - Jingbin Wang; Zhiliang He; Dongya Zhu; Zhiqian Gao; Xiaowei Huang; Quanyou Liu (Geofluids)
The third member (M3) of the Upper Permian Pusige Formation is a prominent organic-rich lacustrine mudstone sequence within the Yecheng-Hetian Sag, Tarim Basin, hosting major petroleum resources. However, its depositional history and organic matter (OM) enrichment mechanism have received little attention. Therefore, various organic and inorganic geochemical analyses were performed on thirty-four core samples from the Well DW1, to elucidate their depositional paleoenvironments, provenance, and tectonic setting, as well as the controlling factors of OM enrichment. Results showed that the M3 mudstones are classified as poor- to fair-quality hydrocarbon source rocks with mature type II-III kerogen, considering their low organic geochemical parameters. Paleosalinity indexes (e.g., Beq, Sr/Ba, and B/Ga) indicated the typical high-saline lacustrine water body, in which redox state was the oxic-dysoxic as suggested by multiple indicators. Many paleoclimate and weathering proxies suggest a dominant semiarid condition and low weathering degree in the Yecheng-Hetian Sag, which led to that weathered felsic rocks from the West Kunlun Orogen to the southwest of basin were quickly transported into the lake basin. Detrital materials carrying nutrient elements finally promoted the development of relatively high paleoproductivity indicated by fairly high P/Ti and Ba/Al ratios. The negative relationship between P/Ti and total organic carbon (TOC) indicates that paleoproductivity was not the main controlling factor. The correlations among TOC and P/Ti and other multiple proxies suggest that the OM enrichment can be interpreted as both the “preservation model” and “dilution model.” Although the water body was relatively oxygen-riched, high sedimentation rate could largely shorten the exposure time of OM with oxygen, thus decreased the decomposition of OM. In particular, the high-saline, stratified lake water may also restrain the degradation of OM. Furthermore, detrital dilution exerted a potential effect on TOC abundances. On the basis of the above results, a developing model was established to decipher the formation mechanism of OM in these M3 mudstones.